INTERNALISASI NILAI MODERASI BERAGAMA DALAM POLA PENGEMBANGAN KURIKULUM TERINTEGRASI DI MADRASAH ALIYAH DARUL ‘ULUMISSYAR'IYYAH - Nur Widyasari; Khusnul Mazidah; Muhammad Hadziq 'Aqil; Muhamad Bisri Ihwan; Achmad Faizal Ababil (STKIP Pesisir Selatan, 2026)
Internalizing the value of religious moderation is a strategic need in facing the challenges of ideological polarization and strengthening the character of students in the madrasah environment. This study aims to analyze the pattern of integrated curriculum development in internalizing the value of religious moderation at Madrasah Aliyah Darul 'Ulumissyar'iyyah. The study uses a qualitative approach with a case study type that focuses on the managerial and pedagogical mechanisms in the implementation of the integrated curriculum. Data collection techniques were carried out through in-depth interviews with madrasah leaders, teachers, and the student affairs and guidance and counseling department, direct observation of madrasah academic and cultural activities, and documentation studies of curriculum documents, syllabi, observation journals, and student attitude development reports. Data analysis was carried out descriptively and analytically with an integrative-interconnective model through the process of data reduction, data presentation, and drawing conclusions strengthened by source triangulation. The research results show that the internalization of religious moderation values ​​was successfully realized through three main strategies: the implementation of an integrated curriculum that eliminates the dichotomy between religious and general knowledge, the transformation of teachers' roles as living curriculum that exemplifies moderation in daily life, and the implementation of authentic behavioral and affective-based evaluations.